A Form of Independent Curriculum, an Overview of Independent Learning at State Elementary School 05 Gelumbang Muaraenim - Mustafiyanti, Mustafiyanti; Putri , Mesi Pramesia; Muyassaroh, Muyassaroh; Noviani, Dwi; Dylan, Moatti (Pengabdian: Jurnal Abdimas, 2023)
Background. The Merdeka Curriculum as an alternative curriculum overcomes learning setbacks during the pandemic which gives "Independent Learning" freedom to learning implementers, namely teachers and principals in compiling, implementing the learning process, and developing curriculum in schools paying attention to the needs and potentials of students. Purpose. This research was conducted to provide an overview of the Merdeka Curriculum as a form of independent learning in elementary schools regarding the profile of Pancasila students, the structure of the Merdeka Curriculum in elementary schools, and the teaching tools used. Method. The research was conducted using the Library Research method (literature study) and visited a website that presents information related to the Independent Learning Curriculum in elementary schools. Results. In preparation for the implementation of the Merdeka Curriculum, teachers need to learn more about the Merdeka Curriculum and consider projects according to student phases in order to achieve meaningful, profound, and fun learning outcomes as well as students. Conclusion. The Merdeka Curriculum with the concept of independent learning in elementary schools provides "independence" for education implementers, especially teachers and principals, in compiling, developing and implementing the curriculum based on the potential, and needs of students and schools.